Exploring the Anticancer Activity of Gold Complex with Newly Ligand (DDIBM): Synthesis, Spectral Identification and Magnetic Susceptibility of Its Metallic Complexes - Noor, Siham Sami; Kareem, Ibtihal Kadhim (Universitas Gadjah Mada, 2024)
The new heterocyclic ligand, 5-(dimethylamino)-2-(((2-((E)-(4,5-diphenyl-1H-imidazol-2-yl)diazenyl)benzyl)imino)methyl)phenol (DDIBM), was synthesized via the condensation of p-aminobenzylamine with 4,5-diphenyl imidazole, and the resultant compound was condensed with 4-(dimethylamino)-2-hydroxybenzaldehyde. Various instrumental techniques such as mass, 1H-NMR, IR, C.H.N elemental analysis, and UV-vis spectroscopy were used to analyze a newly synthesized ligand. A novel series of complexes was prepared by complexing the ligand with Ni(II), Cu(II), Co(II), and Au(III) and characterized using some of the mentioned techniques. Flame atomic absorption spectroscopy was used to measure the metal ion percentages in the complexes. The magnetic susceptibility and molar conductivity were studied. The electronic spectral data and the magnetic measurement predict the octahedral structure of the complexes except Au(III) complex which has square planer geometry. All complexes showed electrolyte properties. This study aimed to conduct an in vitro cytotoxicity comparative study of DDIBM and its Au(III) complex on human breast cancer cells (MCF-7) and other normal cells. The Au(III) complex was found to be highly selective in targeting cancer cells without affecting normal healthy cells, compared to the ligand. Thus, this complex can be considered as a new drug for treating breast cancer cells (MCF-7), and an attempt in the future to study its effect on other types of cancer.